Designing an Accounting System for Toko Asean Motor - Ivone Ivone; Jevyyanti Jevyyanti (Universitas Internasional Batam, 2023)
Abstract This activity aims to create an accounting system to help micro-business entrepreneurs on accounting records and financial reports which reflect the business situation. The object of this activity is Toko Asean Motor, which still uses manual records, instead of a system which can lead to human error, and also not having a good financial report. The method that will be applied in this research begin with conducting surveys and interviews at business locations. Next, designing an accounting system according to the needs of the business. Before designing, observations or discussions will be carried out with the person in charge to determine the operational cycle of the business. Next, the implementation stage will be carried out and the last step is for the business party to provide an assessment of whether the system that has been designed is sufficiently helpful or not. This activity results in an accounting system designed in Microsoft Access program so that entrepreneurs can easily do the records such as sales, purchases of inventory, supplies and others operational records and the system can automatically create financial reports such as profit and loss, changes in equity, statements of financial position. This system can also improve business flow to a more efficient and effective business operation and this system can be useful for this business as a basis for decision making.